School Leadership Policy and Early Literacy–Numeracy Development in Indonesian Early Childhood Education: A Case Study of the Merdeka Curriculum - Mufida Gunawati (AL-ISHLAH: Jurnal Pendidikan, 2026)
This study examines how principal leadership policy supports early literacy and numeracy development in Indonesian early childhood education (PAUD) through the implementation of the Merdeka Curriculum. Employing a qualitative case study design, the research was conducted in selected PAUD institutions in Indonesia that had actively implemented the Merdeka Curriculum. Data were collected through semi-structured interviews with principals and teachers, classroom observations, and analysis of curriculum plans, lesson plans, and school policy documents. The data were analyzed using thematic analysis involving open, axial, and selective coding to identify recurring patterns and explanatory themes. The findings reveal that principal leadership policy influences literacy and numeracy development indirectly by shaping classroom practices, teacher instructional capacity, and assessment processes rather than directly affecting children's learning outcomes. Effective leadership was enacted through five interrelated mechanisms: fostering pedagogical coherence, strengthening teacher professional capacity, integrating literacy and numeracy into play-based learning, aligning formative assessment with developmental principles, and promoting active parent and community engagement. The study further shows that the enactment of leadership policy is constrained by variations in leadership capacity, institutional resources, and tensions between developmental approaches and academic expectations. Conceptually, this study positions principal leadership policy as a mediating mechanism that connects curriculum enactment with instructional practices and children's early literacy and numeracy development, thereby extending current perspectives on educational leadership within the implementation of the Merdeka Curriculum.